DOES NICKEL INFLUENCE LEAF NITROGEN UPTAKE IN COFFEE SEEDLINGS? - Bruno, Isabeli Pereira; Moraes, Milton Ferreira; Damin, VirgÃnia; Dourado-Neto, Durval; Reichardt, Klaus (REVISTA DE AGRICULTURA, 2019)
Nickel is an essential element in plants, mainly acting as a component of the urease enzyme. Therefore, its use in foliar solutions could increase nitrogen use efficiency. This work aimed to evaluate leaf nitrogen absorption in coffee seedlings (1-year-old), using two nitrogen application rates with nickel presence or absence, during 24 hours. The results showed, however, that nickel addition to the leaf solution impairs the absorption of nitrogen, at least on the first day after application.